Analisis Kompetitif dan Spesialisasi Sektor Unggulan Di Kabupaten Kotabaru - Adawiah, Rabiatul; Wardhana , Ali (PPJP ULM, 2021)
This research was conducted for (1) analyzing the growth of the economic sector and the competitiveness of economic sectors in the kotabaru disctrict.; (2) determine the excellent sector in the Kotabaru district to be prioritized in regional development. Variable in this research is PDRB economic sector from 2011 to 2018. Data is processed by shift share analysis. The results if this research mentioned that the growth of economic in the Kotabaru disctrict in end of 2018 which is analyzed by shift share analysis generated conclusions that mine and excavation sector, transportation and warehousing sector, provision of accommodation and food sector, information and communication sector, company services sector, education services sector, health services and social activities sector and other services sector have hih competitiveness and spesialitazion. While the sectors that indicated have the best speed of growth is processing industry sector and other services sector